The RenTg Mice: A Powerful Tool to Study Renin-Dependent Chronic Kidney Disease - Huby, Anne-Cecile (Public Library of Science, 2012)
BACKGROUND: Several studies have shown that activation of the renin-angiotensin system may lead to hypertension, a major risk factor for the development of chronic kidney disease (CKD). The existing hypertension-induced CDK mouse models are quite fast and consequently away from the human pathology. Thus, there is an urgent need for a mouse model that can be used to delineate the pathogenic process leading to progressive renal disease. The objective of this study was dual: to investigate whether mice overexpressing renin could mimic the kinetics and the physiopathological characteristics of hypertension-induced renal disease and to identify cellular and/or molecular events characterizing the different steps of the progression of CKD. METHODOLOGY/PRINCIPAL FINDINGS: We used a novel transgenic strain, the RenTg mice harboring a genetically clamped renin transgene. At 3 months, heterozygous mice are hypertensive and slightly albuminuric. The expression of adhesion markers such as vascular cell adhesion molecule-1 and platelet endothelial cell adhesion molecule-1 are increased in the renal vasculature indicating initiation of endothelial dysfunction. At 5 months, perivascular and periglomerular infiltrations of macrophages are observed. These early renal vascular events are followed at 8 months by leukocyte invasion, decreased expression of nephrin, increased expression of KIM-1, a typical protein of tubular cell stress, and of several pro-fibrotic agents of the TGFβ family. At 12 months, mice display characteristic structural alterations of hypertensive renal disease such as glomerular ischemia, glomerulo- and nephroangio-sclerosis, mesangial expansion and tubular dilation. CONCLUSIONS/SIGNIFICANCE: The RenTg strain develops CKD progressively. In this model, endothelial dysfunction is an early event preceding the structural and fibrotic alterations which ultimately lead to the development of CKD. This model can provide new insights into the mechanisms of chronic renal failure and help to identify new targets for arresting and/or reversing the development of the disease.